PARTIAL REWINDING COIL PADA GENERATOR UNIT 6 PLTD AMPENAN MENGGUNAKAN STANDAR IEEE - Sambodo Rila Priambudi; Teguh Utomo; Mahfudz Shidiq (Jurnal Mahasiswa TEUB, 2023)
PLTD Ampenan is one of power plant that generated by diesel power that located at Mataram City, West Nusa Tenggara. PLTD Ampenan has 8 units generators with total power 37.5 MW. Unit 6 of PLTD Ampenan is a synchronous generator with 9900 kVA or 8MW capacity. In October 2019 there’s accident in generator unit 6. After the investigation, winding stator found to be damaged that cause top bar coil part to be short-circuited. Action that taken for this problem is partial rewinding coil to the damaged coil. In this study will be known how to do partial rewinding coil and observe the effect to generator unit 6 PLTD Ampenan. By applying IEEE standard for partial rewinding coil, there’s discrepancy standard when testing polarity index at pra comissioning stage.However, by agreement from user, the progress can continue to comissioning stage with notes voltages that given to generator supplied step by step. After completing all stages of partial rewinding coil, generator stated running well. Based on analysis between output data before generator damaged and output data after generator repaired, the value of voltage, frequency, and power factor tend to be the same like generator before damaged. Current that flowing in each phase declared balanced because the value of coil resistance of each phase did not exceed the limit of deviation from it’s average which is ±2%. While on load power has increased after partial rewinding coil with the same excitation supply.Keywords: partial rewinding coil, IEEE standards, generator repair